Performance of a modified paddy transplanter planting finger for system of rice intensification - Ibrahim, Bala (2015)
Problems associated with sustainable and affordable rice production has been a challenge due to scarcity of water and water related resources. The overall objective of this research was to develop a new approach to increase rice production with the limited resources input through management practices that simultaneously provide better growth condition. Two case studies were carried out at (i) experimental field located in the campus of Universiti Putra Malaysia and (ii) Tanjung Karang. The purpose of both case studies was to evaluate a management practice method known as System of Rice Intensification (SRI). Main SRI management practices such as planting depth, missing hill, hill population, number of seedling per hill, soil characteristics of the sites, and moisture content were evaluated using a modified transplanter. The planting finger of the transplanter was modified. The effects of different hill-spacings on 14-days old seedlings of MR219 rice variety were studied using analysis of variances. The experiment was designed at three seeding rates (70g,75g and 240g) per tray. The plant characteristics at transplanting time consisted of 2 to 3 number of leaves, 2 mm stem thickness, 19 mm stem length and 3.5 mm root length. The machine was operated at a field capacity of 0.04ha/hr, field efficiency of 84% using shift lift gear position 3, and transplanting at 3 mm depth. The plantingparameter showed that increase in spacing results in more tillers and more panicles per plant, while hill population and empty grains increases with decrease in spacing. The result of this research showed that the soil clay silt loam with a PH values of 7.5 and 5.0 and a bulk density of 0.86g/cm3 and 0.88g/cm3 for Ladang Sepuluh and Tanjung Karang respectively.yield of 9.3 tons per hectare was obtained at a spacing of 24cm x 30cm using a seeding rate of 75g of seeds.